The relationship between system inflammation response index and coronary heart disease: a cross-sectional study (NHANES 2007–2016) - Zhang, Tian Yang; Chen, Hai long; Shi, Yanyu; Jin, Ying; Zhang, Yuan; Chen, Ying (Frontiers in Cardiovascular Medicine, 2024)
Background: Coronary heart disease (CHD) is one of the common chronic diseases in clinical practice, often accompanied by inflammatory reactions. In recent years, the system inflammation response index (SIRI) has aroused researchers' interest as a novel inflammatory biomarker. This study aims to explore the relationship between the SIRI and CHD through the National Health and Nutrition Examination Survey (NHANES) database.We conducted a cross-sectional study and analyzed participants aged 40 and above with complete data from the NHANES survey years 2007-2016. Logistic regression analysis was used in this study to explore the relationship between the risk of CHD and SIRI. Stratified subgroup analysis was conducted based on age, gender, race, education level, body mass index (BMI), smoking status, drinking, hypertension, diabetes and angina pectoris to evaluate the relationship between SIRI and CHD in different populations. Additionally, restricted cubic spline (RCS) analysis was employed to investigate whether there is a nonlinear association between SIRI and CHD.Results: A total of 6374 eligible participants were included, among whom 387 were diagnosed with CHD. The SIRI levels in the CHD group were significantly higher than those in the non-CHD group. After adjusting for potential confounders, an elevated SIRI level was associated with an increased risk of CHD, with an odds ratio of 1.12, 95% CI: (1.03,1.22), P=0.008. Subgroup analysis results indicated a significant interaction between SIRI and CHD among genders (P for interaction < 0.05), especially in females. In contrast, no significant interaction was observed among age, race, education level, BMI, smoking status, drinking, hypertension, diabetes and angina pectoris (P for interaction > 0.05). The RCS analysis showed a significant linear relationship between SIRI and CHD (P for non-linearity > 0.05), with an inflection point at 2.86.Our study indicates that an elevated system inflammation response index is associated with a higher risk of CHD. Particularly among women.